PORTRAIT OF THE LGBT PHENOMENON: A REVIEW OF INDONESIAN ISLAMIC DISCOURSE - Rustriningsih (UIN Raden Mas Said Surakarta, 2025)
The LGBT phenomenon is increasingly prominent and even the perpetrators openly expose themselves to get recognition and legality of their existence. Their demands for their existence reap the pros and cons in various circles and become a polemic, including in Indonesia. This research aims to examine the LGBT phenomenon in the Indonesian context, with a particular emphasis on the perspectives of Indonesian Islamic figures and organizations on the phenomenon. The data collection method used in this research is a literature study, with data collection techniques through the collection and analysis of various literature related to the research theme, including books, journal articles, websites, Youtube channels and other sources relevant to the topic of LGBT in the Indonesian context. The research findings show that despite strong social resistance, there is a need for a balanced approach between religious values and human rights in dealing with this phenomenon. In this case, human rights become one of the bases for groups that support the existence of LGBT. However, in general, Indonesia with the majority of its population embracing Islam, the existence of LGBT on the basis of religion is firmly rejected, with the statement that the act violates the human nature given by God. The rejection is also supported by several perspectives that review the mudharat of LGBT actions. The theoretical implication of this research is the need for a balanced approach between religious values and human rights in dealing with the LGBT phenomenon in Indonesia, which reflects a fundamental challenge in harmonizing human rights universalism with the context of strong religious values.